2021
DOI: 10.3934/dcdss.2020279
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization analysis of drive-response multi-layer dynamical networks with additive couplings and stochastic perturbations

Abstract: This paper concerns the synchronization of a kind of drive-response multi-layer dynamical networks with additive couplings and stochastic perturbations. Multi-layer networks are a kind of complex networks with different layers, which consist of different kinds of interactions or multiple subnetworks. Additive couplings are designed to capture the different layered connections. In this paper, two pinning controllers are designed to guarantee the synchronization of the stochastic multi-layer network. One is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In addition, there is also outer synchronization, which refers to synchronization between different complex networks. The outer synchronization researches in complex networks can be found in the literature [12][13][14]. For the outer synchronization of the single-layer networks, Wang et al [12] studied the synchronization between two delay-coupled complex dynamical networks with a noise perturbation using an adaptive controller.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is also outer synchronization, which refers to synchronization between different complex networks. The outer synchronization researches in complex networks can be found in the literature [12][13][14]. For the outer synchronization of the single-layer networks, Wang et al [12] studied the synchronization between two delay-coupled complex dynamical networks with a noise perturbation using an adaptive controller.…”
Section: Introductionmentioning
confidence: 99%
“…Hymavathi et al [13] introduced an outer synchronization scheme for fractional-order neural networks with time delays, and derived several criteria achieving synchronization between the drive and response systems based on fractional inequalities and Lyapunov-type functions. Zhuang et al [14] used drive-response methods to study the synchronization of multi-layer dynamical networks with additive delay couplings and stochastic perturbations, and obtained sufficient conditions for synchronization between the drive and response networks using pinning controllers. In the existing work of outer synchronization in complex networks, one usually designs some suitable control protocols to drive the synchronization of networks.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, noise plays an important role in synchronization since it can stabilize an unstable system. In recent years, many scholars are very interested in synchronization of stochastic networks with time-varying delays [2,[29][30][31][32][33][34][35][36][37][38]. In 2013, the Jensen integral inequality was improved by the so-called Wirtinger-based integral inequality [33].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Gao et al [29] showed that a state feedback controller and an adaptive updated law used to guarantee stochastic memristor-based neural networks with noise disturbance can be asymptotically synchronized. In [38], the authors investigated the synchronization of a stochastic multilayer dynamic network with time-varying delays and additive couplings by designing two pinning controllers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, neurals networks have attracted a lot of researchers in different research areas [20,21,4,27,7,8]. It is worth mentioning that MCNNs with different time scales, which are extensions of conventional neural networks.…”
mentioning
confidence: 99%